Clostridium difficile Infection Prevention Bundle Implementation. (October 2020) - Ling, Moi Lin; Jin, Pinhong; Tan, Kwee Yuen
Abstract : Background: The optimal prevention of healthcare onset Clostridium difficile infection (CDI) has been a challenging one in an acute tertiary-care hospital with limited number of single rooms. Asymptomatic patients with CDI are nursed in open wards but tagged with a green sticker to alert staff of their status. This signal prompts cleaning staff to use 5, 000 ppm sodium hypochlorite to clean environmental surfaces in the multibed room and to continue with modified contact precautions. Methods: We conducted a survey on infection prevention measures used in the management of CDI patients over 2 weeks among senior nurse managers, clinicians, and registered nurses in 38 inpatient wards. We categorized the survey results into 4 types of practices: established practices, nonestablished practices (easy implementation), nonestablished practices (lack of resources), and nonestablished practices (staff resistance). We then identified barriers to determine reasons for resistance to nonestablished practices before the implementation of the CDI bundle in May 2019. The bundle comprised the following components: contact precautions, antimicrobial stewardship, isolation of CDI patient with diarrhea in single room, environment, and equipment hygiene. Following the survey, we enhanced the signage for CDI patients to be more obvious. Monthly, we monitored the incidence of HO- Clostridium difficile to assess effectiveness of implementation measures. Results: Nonestablished practices (easy implementation) included uncertainty of diarrhea definition and the recommended environmental hygiene disinfectant, lack of understanding of the importance of complying to personal protective equipment (PPE), and inconsistency in conveying CDI status. Among nonestablished practices (lack of resources), shortage of isolation beds for CDI patients with diarrhea and unavailability of electronic alert system for CDI patients within the institution are the major issues faced by clinical staff. Unavailability of CDI indicator stickers, contact precaution posters, and sporicidal wipes were noted in 6 medical and surgical wards. Nonestablished practices (staff resistance) were related to the time taken to don full PPE and reluctance to arrange for an isolation bed due to increased workload and unavailability of isolation beds. A shift was noted in the control chart for HO- Clostridium difficile after the implementation of the CDI bundle in May 2019. Conclusions: The categorization of practices into established and nonestablished practices can help to identify barriers that may interfere with successful implementation of an infection prevention bundle. Funding: None Disclosures: None